Tetraammineplatinum(II) and Tetraamminepalladium(II) Chromates as Precursors of Metal Oxide Catalysts. Issue 19 (9th March 2020) - Filatov, Evgeny; Lagunova, Varvara; Potemkin, Dmitry; Kuratieva, Natalia; Zadesenets, Andrey; Plyusnin, Pavel; Gubanov, Alexander; Korenev, Sergey
Abstract: [M(NH3 )4 ]A (M=Pt, Pd; A=CrO4, Cr2 O7 ) and [Pt(NH3 )4 (NO2 )(Cr2 O7 )]NO3 complex salts were synthesized and characterized by a number of physicochemical methods of analysis (IR, single‐crystal and powder XRD, and simultaneous thermogravimetry and differential scanning calorimetry with evolved gas analysis mass spectrometry). Thermolysis of the salts obtained in a hydrogen atmosphere proceeds with the partial reduction of chromium to a metallic state and the formation of M x Cr1− x (M=Pt, Pd) metal solid solution with a chromium content of up to 22 at % and chromium(III) oxide. The thermal decomposition of salts in an inert and oxidizing atmosphere passes through the formation stage of the MCrO2 phase with the delafossite structure followed by its subsequent decomposition into chromium(III) oxide and noble metal. Nanosized Pt−Cr2 O3 and Pd−Cr2 O3 composites obtained by the thermolysis of precursor salts in air at 500 °C and being held at this temperature for 1 h showed a high catalytic activity in the CO total oxidation (TOX) and preferential oxidation in the excess of hydrogen (PROX) processes compared with that of monometallic Pt and Pd powders. Abstract : [M(NH3 )4 ]A (M=Pt, Pd; A=CrO4, Cr2 O7 ) and [Pt(NH3 )4 (NO2 )(Cr2 O7 )]NO3 complex salts were synthesized and the thermal decomposition mechanisms of precursors in different atmospheres were studied. The catalytic properties of bimetallic Pt−Cr2 O3 and Pd−Cr2 O3 were compared with those of monometallic Pt and Pd in CO total oxidation and preferential oxidation in excess hydrogen processes.